Comparing the effects of corn fermented protein with traditional distillers dried grains fed to healthy adult dogs on stool quality, nutrient digestibility, and palatability - Kilburn-Kappeler, Logan R.; Lema Almeida, Krystina A.; Paulk, Chad B.; Aldrich, Charles G. (Frontiers in Animal Science, 2023)
Traditional distillers dried grains, co-products from the ethanol industry, can be utilized as sustainable ingredients for pet food. However, negative consumer perception prevents their widespread use. Corn fermented protein (CFP) is produced using post-fermentation separation technology, resulting in a high protein ingredient, which may increase consumer appeal compared to traditional distillers dried grains. The study objective was to compare the effect of CFP with that of traditional distillers dried grains on stool quality, nutrient digestibility, and palatability when fed to dogs. The control diet (CON) contained 15% soybean meal and the experimental diets contained 3.5% brewer’s dried yeast (BDY), 2.5% brewer’s dried yeast plus 17.5% distillers dried grains with solubles (BDY+DDGS), or 17.5% corn fermented protein (CFP). Experimental diets were fed to adult dogs (n = 12) in a 4 × 4 replicated Latin square design. Dogs were adapted to the diets for 9 days; this was followed by 5 days of total fecal collection. Titanium dioxide (0.4%) was added to all diets as an external marker to estimate digestibility. Data were analyzed using a mixed model in SAS, with treatment as a fixed effect and dog and period as random effects. Fecal output was greatest (p< 0.05) for dogs fed BDY+DDGS. The feces of dogs consuming CFP were firmer (p< 0.05) than those of dogs consuming CON and BDY+DDGS. Overall, nutrient digestibility was greatest (p< 0.05) for CON and BDY and lowest for BDY+DDGS, with that for CFP being intermediate. There were no differences (p > 0.05) in total short-chain or branched-chain fatty acid concentrations in the fresh fecal samples of dogs fed these dietary treatments. However, the percentage of propionate was higher (p< 0.05) in the fecal samples of dogs fed CON than in those of dogs fed BDY+DDGS, whereas the percentage of valerate was higher (p< 0.05) in the fecal samples of dogs fed CON than in those of dogs fed CFP. In the palatability evaluation, dogs had no preference when CON was compared with BDY or BDY+DDGS. However, dogs appeared to prefer CON over CFP. Overall, CFP resulted in improved stool quality and nutrient digestibility when compared with DDGS, which could increase consumer appeal for inclusion into pet food. The impact of CFP on palatability, however, warrants further investigation.